(untitled) (Palimpsesto, 2026)
This text introduces the special issue "Feminisms, Utopias, and Politics of the Commons" by asking a central question: who sustains life when the material, institutional, and communal conditions that make it possible are increasingly threatened? In a Latin American context shaped by neoliberal expansion, the crisis of care, and multiple forms of extractivism and violence, the reflection on the commons gains renewed urgency. Drawing on feminist economics, community feminism, and decolonial perspectives, the text proposes to understand the commons not as a preexisting object but as a political principle constructed through collective practices of cooperation, care, and the production of life. Far from offering an abstract definition, the dossier shows how the commons are produced, sustained, and contested in situated experiences: mutual care among older women, support networks in rural contexts, agroecological pedagogies, psychosocial accompaniment with Mapuche Lafkenche women leaders, and memory practices that resist forgetting. A joint reading of the articles reveals that the commons are neither a starting point nor a normative horizon but a permanent construction that gains density precisely where life is most vulnerable. Nevertheless, the dossier maintains an indispensable critical tension: recognizing the political potential of these experiences does not imply romanticizing communities or naturalizing the fact that women once again disproportionately shoulder the work of sustaining life. Instead, it calls for strengthening articulations among social organizations, public institutions, universities, and communities in order to collectively redistribute the responsibilities essential for the reproduction of life, reminding us that no life is sustained in solitude.